The Effect of Earnings Per Share and Dividend Per Share on the Market Price Per Share of Listed Commercial Banks on the Nepal Stock Exchange - Khadka, Kamal Kumar; Gaire, Laxman Prasad (Journal of Entrepreneurship & Management Studies, 2024)
This study targeted to evaluating the impact of earnings per share (EPS) and dividend per share (DPS) on the market price per share (MPPS) of commercial banks that were listed on the Nepal stock exchange. Over a span of seven years, from 2016-2017 to 2022-2023, the study used a comprehensive dataset consisting of 210 panel data observations were meticulously compiled from the financial records of 10 commercial banks, selected from a total of 20 operating in Nepal. Descriptive statistics were conducted, and multiple linear regression models were also used to examine the effect of earnings per share and dividend per share on the market price per share. The findings of the regression analysis showed that while EPS and DPS account for 20.80 percent of the variation in MPPS, other factors account for 79.20 percent of the variation. Further, the outcome indicates that DPS and EPS have a statistically significant and favorable effect on MPPS. The study came to the conclusion that the DPS and EPS are important determinants of stock price and that they have a significant effect on Nepalese commercial banks’ MPPS.